Absence of non-local manipulation of oxygen atoms inserted below the Si(111)-7x7 surface - Richard Cobley (Langmuir, 2020)
The injection of electrons from the scanning tunneling microscope tip can be used to perform nanoscale chemistry and study hot electron transport through surfaces. While nonlocal manipulation has been demonstrated primarily for aromatic adsorbates, here we confirm that oxygen atoms bonded to the Si(111) surface can also be nonlocally manipulated, and we fit the measured manipulation data to a single channel decay model. Unlike aromatic adsorption systems, oxygen atoms also insert below the surface of silicon. Although the inserted oxygen can be manipulated when the tip is directly over the relevant silicon adatom, it is not possible to induce nonlocal manipulation of inserted oxygen atoms at the same bias. We attribute this to the electrons injected at +4 eV initially relaxing to couple to the highest available surface state at +3.4 eV before laterally transporting through the surface. With a manipulation threshold of 3.8 eV for oxygen inserted into silicon, once carriers have undergone lateral transport, they do not possess enough energy to manipulate and remove oxygen atoms inserted beneath the surface of silicon. This result confirms that nonlocal nanoscale chemistry using the scanning tunneling microscope tip is dependent not only on the energy required for atomic manipulation, but also on the energy of the available surface states to carry the electrons to the manipulation site.